Can helicopter parenting be beneficial for parent–child relationships? A person-centered approach in the United States and South Korea - Hwang, Woosang; Jung, Eunjoo; Kim, Seonghee; Hadi, Narges (Frontiers in Psychology, 2023)
We aimed to uncover latent classes of maternal and paternal helicopter parenting among American and Korean college students and to examine whether latent classes of maternal and paternal helicopter parenting are associated with parent-child relationships. We conducted three-step latent class analyses using five helicopter parenting indicators for 433 mother-child and 401 father-child groups in the United States and 207 mother-child and 195 father-child groups in South Korea. We identified the same three helicopter parenting latent classes (strong, weak, and managed) in mother-child and father-child groups in the United States and Korea. In addition, we found that American and Korean college students in strong and managed helicopter parenting latent classes reported better parent-child relationships than those in the weak class regardless of parents’ gender. Our findings indicate that helicopter parenting is multidimensional and can be similarly interpreted by college students in Western and Eastern societies. Further, our findings suggest that helicopter parenting could be helpful for college students to establish an intimate relationship with their parents.